The role of new media tools in democratic change in the Kurdistan region Descriptive study - Sartep Waysi Kareem; Muhammad Qadr Mawlud (Zanco Journal of Humanity Sciences)
The role of forms, or new media tools, has been directed at all sectors and parts of life and all questions and issues within the community, especially the political and democratic process. That's why the researcher in this research tried scientifically and academically to explain that some new media tools had an emphasis on democratic change and the process of democraticization of the community, which is the main goal of the research.